Delay from fracture to hospital admission: a new risk factor for hip fracture mortality? - Vidal, Edison Iglesias de Oliveira [UNESP]; Moreira-Filho, D. C.; Pinheiro, R. S.; Souza, R. C.; Almeida, L. M.; Camargo, K. R.; Villas Bôas, Paulo José Fortes [UNESP]; Fukushima, Fernanda Bono [UNESP]; Coeli, C. M. (Springer London Ltd, 2012)
The relationship between surgical timing and hip fracture mortality is unknown in the context of developing countries where large delays to surgery are common. We observed that delay from fracture to hospital admission is associated with decreased survival after a hip fracture.To examine the relationship between the time interval from fracture to surgery as well as its subcomponents (time from fracture to hospital admission and time from admission to surgery) and hip fracture survival.The medical records of all patients aged 60 years and older admitted to a public university hospital in the city of Rio de Janeiro with a primary diagnosis of hip fracture between 1995 and 2000 were reviewed. Survival to hospital discharge and at 1 year were examined.Among 343 patients included in the study, there were 18 (5.3%) in-hospital deaths, and 297 (86.6%) patients remained alive 1 year after surgery. Very long delays from the time of fracture to hospital admission (mean 3 days) and from hospital admission to surgery (mean 13 days) were identified. Increased time from fracture to hospital admission was associated with reduced survival to hospital discharge (hazard ratio [HR] 1.09, 95% CI 1.03-1.15, p = 0.005) and reduced survival at 1 year after surgery (HR 1.07, 95% CI 1.03-1.10, p < 0.001). The interval of time from hospital admission to surgery was not associated with reduced survival to hospital discharge (HR 1.03, 95% CI 0.96-1.10, p = 0.379) or at 1 year after surgery (HR 1.03, 95% CI 0.99-1.07, p = 0.185).If the association estimated in our study is causal, our results provide evidence that some hip fracture-related deaths could be prevented by improved patient access to appropriate and timely hospital care in the context of a developing country.
Keywords: Aged; Brazil; Developing countries; Hip fractures; Mortality; Risk factors